2008
DOI: 10.22358/jafs/66469/2008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phytogenic substances on growth performance, digestibility of nutrients, faecal noxious gas content, blood and milk characteristics and reproduction in sows and litter performance

Abstract: Forty sows (Landrace×Yorkshire), with an average body weight (BW) of 184.5 kg and average parity of 2.65, were used to determine the effects of a phytogenic feed additive (PFA) on growth performance, digestibility of nutrients, faecal NH 3 -N gas content, blood and milk characteristics and litter performance. Dietary treatments included: 1. control (CON) and 2. PFA (basal diet + 0.04% phytogenic feed additive). Digestibility of dry matter (DM) was increased signifi cantly (P<0.05) in PFA treatment. Faecal ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…Application of plant-derived feed additives positively affects daily weight gains, feed intake and feed conversion ratio (Wang et al, 2008). This correlation was observed in the present studies, 15 and 30 g of LPC preparation per kilogram of feed promoted the growth of sow body weight in late gestation (Trial I), whereas in the groups fed LPC periodically, only the sows with the lucerne preparation supplied during gestation had a higher prepartum body weight.…”
Section: Discussionsupporting
confidence: 85%
“…Application of plant-derived feed additives positively affects daily weight gains, feed intake and feed conversion ratio (Wang et al, 2008). This correlation was observed in the present studies, 15 and 30 g of LPC preparation per kilogram of feed promoted the growth of sow body weight in late gestation (Trial I), whereas in the groups fed LPC periodically, only the sows with the lucerne preparation supplied during gestation had a higher prepartum body weight.…”
Section: Discussionsupporting
confidence: 85%
“…Gertenbach and Bilkei (2001) reported that giving feed supplemented with 60 g carvacrol and 55 g thymol per ton (1000 ppm Oregpig) during the postweaning period significantly improves the weight gain and health of pigs. Wang et al (2008), on the other hand, found no significant differences in the performance of piglets from sows fed with PFA from 7 days prior to farrowing until the end of lactation, probably due to the short duration of the supplementation. Our results on performance agree with Asghar et al (1991), who reported a daily gain improvement in post-weaning piglets fed with a natural antioxidant and vitamin E. Other botanicals (herbs and/or spices) administered as feed additives have shown a similar improvement in feed conversion (Maass et al, 2005).…”
Section: Growth Performancesmentioning
confidence: 72%
“…The back-fat thickness (BFT) of the sows (6 cm off the midline at the 10th rib) was measured using a real-time ultrasound instrument (Piglot 105, SFK Technology, Herlev, Denmark) before farrowing, few hours after farrowing and at weaning to determine back-fat loss. Values from the two measurements were averaged to obtain a single BFT measurement (Wang et al 2008). Detection of oestrus was conducted twice daily (08:00 and 16:00 h) from weaning onwards.…”
Section: Sampling and Measurementsmentioning
confidence: 99%